PRUNE1‐related disorder: Expanding the clinical spectrum. Issue 3 (26th June 2018) - Imagawa, E.; Yamamoto, Y.; Mitsuhashi, S.; Isidor, B.; Fukuyama, T.; Kato, M.; Sasaki, M.; Tanabe, S.; Miyatake, S.; Mizuguchi, T.; Takata, A.; Miyake, N.; et al.
Abstract : Neurodevelopmental disorder with microcephaly, hypotonia, and variable brain anomalies (NMIHBA) (OMIM #617481) is an autosomal recessive disease characterized by progressive microcephaly, plagiocephaly, hypotonia, spastic quadriparesis, global developmental delay, intellectual disability, optic features and abnormal brain magnetic resonance imaging (MRI). NMIHBA was recently reported to be caused by PRUNE1 mutations. Eight mutations have been reported in 13 unrelated families. Here, we report 3 PRUNE1 mutations in 1 Caucasian and 3 Japanese families. One recurrent missense mutation (p.Asp106Asn) was previously reported in Turkish and Italian families, while the other 2 mutations (p.Leu18Serfs*8 and p.Cys180*) are novel. We also show that mutant PRUNE1 mRNA can be subject to nonsense‐mediated mRNA decay. The patients presented in this study showed atypical NMIHBA phenotypes with no progressive microcephaly. Furthermore, one Caucasian case had significant macrocephaly; therefore, patients with PRUNE1 mutations can exhibit a broad and heterogeneous spectrum of phenotypes. Abstract : Neurodevelopmental disorder with microcephaly, hypotonia, and variable brain anomalies (NMIHBA) (OMIM #617481) is an autosomal recessive disease characterized by progressive microcephaly, plagiocephaly, hypotonia, spastic quadriparesis, global developmental delay, intellectual disability, optic features and abnormal brain magnetic resonance imaging (MRI). NMIHBA was recently reported to be caused by PRUNE1 mutations. Here, we report 3 PRUNE1 mutations in 1 Caucasian and 3 Japanese families. The patients presented in this study showed atypical NMIHBA phenotypes with no progressive microcephaly. Furthermore, one Caucasian case had significant macrocephaly; therefore, patients with PRUNE1 mutations can exhibit a broad and heterogeneous spectrum of phenotypes.